Fundamental of Entrepreneurship ENT300 : GWRAP / Syaidatul Athirah Ayub ... [et al.] - Ayub, Syaidatul Athirah; Rahman, Sarah; Sabarudin, Nur Afiqah Umira; Hamzah, Nurul Afiqah (2018)
GWRAP offers tortilla wrap for customers, giving a variation of fillings such as the salted egg butter chicken, grilled chicken, and also special fillings during the festive seasons. We are targeting customers from the groups of student to the busy office workers. As we focused on this class of customers, we also provide delivery service to offices if the office workers could not come to us directly. GWRAP marketing strategy is to emphasize the quality and the price of our product. We offer affordable because as we know that if we are selling to school student, they definitely go for the price they can afford while the office workers would likely to get something with good quality and most convenient for them. The management of GWRAP led by 4 managers, each responsible for the administration, marketing, operation and financial of the business. All tasks and duties have been distribute fairly to each one of the managers to ensure that everything in the business is running smoothly.